Highly Toxic Ribbon Worm Cephalothrix simula Containing Tetrodotoxin in Hiroshima Bay, Hiroshima Prefecture, Japan - Manabu Asakawa; Hiroshi Kajihara; Katsutoshi Ito (Toxins, 2013)
In 1998, during a toxicological surveillance of various marine fouling organisms in Hiroshima Bay, Japan, specimens of the ribbon worm, Cephalothrix simula (Nemertea: Palaeonemertea) were found. These ribbon worms contained toxins with extremely strong paralytic activity. The maximum toxicity in terms of tetrodotoxin (TTX) was 25,590 mouse units (MU) per gram for the whole worm throughout the monitoring period. The main toxic component was isolated and recrystallized from an acidified methanolic solution. The crystalline with a specific toxicity of 3520 MU/mg was obtained and identified as TTX by high performance liquid chromatography (HPLC)-fluorescent detection (FLD) (HPLC-FLD), electrospray ionization-mass spectrometry (ESI-MS), infrared (IR), nuclear magnetic resonance (NMR) and gas chromatography–mass spectrometry (GC-MS). The highest toxicity of C. simula exceeded the human lethal dose per a single worm. A toxicological surveillance of C. simula from 1998 to 2005 indicated approximately 80% of the individuals were ranked as “strongly toxic” (≥1000 MU/g). Forty-eight percent of the specimens possessed toxicity scores of more than 2000 MU/g. Seasonal variations were observed in the lethal potency of C. simula. Specimens collected on January 13, 2000 to December 26, 2000 showed mean toxicities of 665–5300 MU/g (n = 10). These data prompted a toxicological surveillance of ribbon worms from other localities with different habitats in Japan, including Akkeshi Bay (Hokkaido) under stones on rocky intertidal beaches, as well as Otsuchi (Iwate) among calcareous tubes of serpulid polychaetes on rocky shores. Within twelve species of ribbon worms examined, only C. simula possessed extremely high toxicity. Therefore, C. simula appears to show generally high toxicity irrespective of their locality and habitat.